Construction and Expression of Recombinant LL-37 as Histag-SUMO Fusion Protein with Factor Xa Cleavage Site - Rostinawati, Tina; Wicaksono, Imam Adi; Sitinjak, Bernap Dwi Putra; Fadhlillah, Muhammad (Bogor Agricultural University, Indonesia, 2024)
LL-37 is an antimicrobial protein expressed by the CAMP gene in humans. This protein has various antibacterial, antiviral and anticancer effects. Expressing LL-37 as a heterologous protein in E. coli cells has its challenges. LL-37 is a peptide that is so small that it must be engineered with a fusion protein to increase its size solubility and prevent proteolysis of the target protein in cells. Factor Xa is the protease chosen to cleave LL-37 from its fusion protein in this research due to leucine binding factor Xa quite strongly. The aim of this study is, therefore, to express LL-37 as a fusion protein with Histaq_SUMO at the N-terminus linked to LL-37 at the C-terminus through Factor Xa cleavage site. Then, the fusion protein was cleaved by Factor Xa to obtain pure LL-37. In this study, LL-37 was produced by recombinant DNA technology, starting with the construction, expression, purification and cleavage of the fusion protein. The constructed genes consisted of 6xHis, SUMO, the factor X cleavage site, and LL-37, a total of 450 bp inserted in the pD451-SR vector plasmid. The results of this study yielded a SUMO_LL-37 protein with a molecular weight of approximately 17.34 kDa, which could be purified by Ni-NTA under native purification conditions. Based on ImageJ SUMO_LL-37 quantification, it was 1.65 µg/µL. LL-37 can be cleaved by factor Xa from SUMO with an enzyme-to-substrate ratio of 1:12.5 at 37°C with a 24-hour incubation time and results as much as 0.144 µg/µL. This article has a related Erratum.